PENGARUH LEVERAGE, PROFITABILITAS, RETURN ON EQUITY DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAPAT DI BURSA EFEK INDONESIA PERIODE 2020 – 2022 - Verlyn Howard; Yosie Mei Four Tami Siagian; Sauh Hwee Teng; Jhon Piter; Paskah Ria Sitorus (Fakultas Ekonomi Prodi Akuntansi, 2024)
This research aimed to analyze the effect of Leverage, Profitability, Return On Equity and Firm Size on Tax Avoidance in manufacturing companies on the Indonesian Stock Exchange in the period 2020-2022. This research uses associative quantitative method. The population of this research were 194 with a sample of 75 which obtained use purposive sampling procedure. The results shows that Leverage and Profitability have an effect on Tax Avoidance in Manufacturing Companies on the Indonesian Stock Exchange for the 2020-2022 period. While Return on Equity and Firm Size have no effect on Tax Avoidance in Manufacturing Companies on the Indonesia Stock Exchange for the 2020-2022 period. The value of the coefficient determination is 0,07, this shows that Leverage, Profitability, Return On Equity and Firm Size was 7% influence on Tax Avoidance while the remaining 93% was explained by other factors than the factors stated in this research. Keyword : Leverage, Profitability, Return on Equity, Firm Size, Tax Avoidance